BOOK NOTICES / BOEKAANKONDIGINGS - Lategan, Bernard C. (Scriptura, 1987)
Brown, David (ed) 1986. The dictionary of Life. Biblical wisdom for modern living. London: Sidgwick & Jackson.Clarkson, Margart 1986. All nature sings. Grand Rapids: Eerdmans.Oates, Wayne E 1985. Managing your stress. Philadelphia: Fortress Press.Monsma, Steven V (ed) 1986. Responsible technology. A Christian perspective. Grand Rapids.Naudé, D F & Sölle, Dorothee 1986. Hope for faith. A conversation. Grand Rapids: Eerdmans.Anderson, Ray S 1986. Minding God’s business. Grand Rapids: Eerdmans.Locke, Hubert g (ed) 1986. Exile in the fatherland. Martin Niemöller’s letters from Moabit Prison. Translated by Ernst Kaemke, Kathy Elias and Jackly Wilferd. Grand Rapids: Eerdmans.Longford, Frank 1986. The Bishops. A study of leaders in the Church today. London: Sidgwick & Jackson.Motlhabi, Mokgethi 1986. Black resistance to Apartheid. A social-ethical analysis. Johannesburg: Skotaville Publishers.Hagan, Lowell & Westerhof, jack 1986. Theirs is the Kindgom. The New Testament. Grand Rapids: Eerdmans.Gaventa, Beverly Roberts 1986. From light to darkness. Aspects of conversion in the New Testament. Philadelphia: Fortress Press.Wink, Walter 1986. Unmasking the powers. The invisible forces that determine human existence. Philadelphia: Fortress Press.Johnson, Luke T 1986. The writings of the New Testament. An interpretation. Philadelphia: Fortress Press.Childs, Brevard S 1986. Old Testament Theology in a canonical context. Philadelphia: Fortress Press.Gowan, Donald E 1986. Eschatology in the Old Testament. Philadelphia: Fortress Press.Miller, Patric D jr 1986. Interpreting the Psalms. Philadelphia: Fortress Press.Vilakazi, Absolom with Methethwa, Bongani & Mpanza, Mthembeni 1986. Shebe. The revitalization of African society. Johannesburg: Skotaville.Cone, James H 1986. Speaking the truth. Ecumenism, liberation, and Black theology. Grand Rapids: Eerdmans.King, Charles H jr 1986. Fire in my bones. Grand Rapids: Eerdmans.Oswalt, John N 1986. The book of Isaiah. Chapters 1-39. Grand Rapids: Eerdmans.Hall, Douglas John 1986. Imaging God. Dominion as stewardship. Grand Rapids: Eerdmans.Mills, Watson E 1986. Speaking in tongues. A guide to research on Glossolalia. Grand Rapids: Eerdmans.